(untitled) (Czech Journal of International Relations, 1999)
Fabrice Fries: Velké evropské rozpravy. HZ Editio, Praha 1998, 369 stran, ISBN 80- 86009-23-9 (z francouzského originálu Les grands débats européens. Édition du Seuil, Paris 1995).